Cell interaction with nanopatterned surface of implants. (August 2010) - Lavenus, Sandrine; Ricquier, Jean-Charles; Louarn, Guy; Layrolle, Pierre
Metals such as titanium and alloys are commonly used for manufacturing orthopedic and dental implants because their surface properties provide a biocompatible interface with peri-implant tissues. Strategies for modifying the nature of this interface frequently involve changes to the surface at the nanometer level, thereby affecting protein adsorption, cell–substrate interactions and tissue development. Recent methods to control these biological interactions at the nanometer scale on the surface of implants are reviewed. Future strategies to control peri-implant tissue healing are also discussed.